New application methods for chromosomal abnormalities screening test using digital PCR - Lee, Seung Yong; Shim, Sung Han; Youn, Jong-Pil; Kim, Seung Jun; Kim, Ji Hoon; Jung, Sung A.; Choi, Hyo Jung; Oh, Moon Ju; Lee, Kyoung-Ryul; Cha, Dong Hyun; Hwang, Seung Yong (Biochip journal, 2015)
The probability of hereditary diseases occurring in the fetus and the childbearing age of the recently-married population have both rapidly increased over the last 10 years. That occupies a large part of such genetic diseases was greater than or equal to the number of chromosomes and genes, the probability of these chromosomal abnormalities occurring increases as the mother’s age increases. Regarding these genetic diseases that are caused by chromosomal abnormalities, it has been possible to reduce the pain of the mother and child if the abnormalities are detected early because schemes can be prepared to address them; therefore, early diagnosis is important. Recently, as part of an analysis that involved the use of very small samples, a digital PCR that allowed for the simultaneous processing of a number of samples was actively developed due to the corresponding advantage. Digital-PCR technology means that a real-time diagnosis with a high sensitivity can be obtained, and it enables the development of a variety of diagnostic techniques-without requiring the use of NGS deep sequencing- through advantages such as digitized measurement results. After extracting the circulating nucleic acid from maternal blood for the screening of fetal DNA, after first confirming that the blood contained fetal DNA, the nucleic acid was selectively applied to the digital PCR for the detection of chromosomal abnormalities, thereby developing a new detection application. The results of 43 samples were analyzed, and the experimental results of the newly developed analytical method show that 9 samples are “high risk,” whereas 34 samples are “low risk.” We consider the accuracy of each test as very reliable. The non-invasive prenatal-screening methods that use digital PCR were developed in this research study due to their lower monetary costs that are derived from an experimental testing time that is less than that of the conventional NGS; provided that the mother is easily accessible, this method can confirm the health status of a fetus. Also, the biomarker knowledge and the analysis methods that were developed in this research study can be applied in chromosomal-abnormality tests. It is expected that the development of a non-invasive examination method to replace the existing invasive testing method will be useful in the improvement of maternal and fetal safety.